Pemanfaatan Bonggol Jagung Sebagai Bahan Campuran Pembuatan Paving block Porous - Firmansyah Ully Pratama; Winda Rahmawati; Febryan Kusuma Wisnu; Siti Suharyatun (abe.fp.unila.ac.id, 2023)
The development needs of the population that continues to increase cause a mismatch in land use. This can make it possible to reduce water catchment areas in any areas with dense building growth. The use of cement in both housing and road construction results in reduced water absorption areas because cement has properties that make it difficult to absorb water, so water will become stagnant. Therefore, a cement substitute is needed to cover the shortage of cement. The addition of corn cobs in the paving block mortar is expected to increase its water absorption without reducing the compressive strength of the paving blocks. This is done to reduce corn cob waste and save on staple food costs. as well as being used as a useful product innovation in reducing corn cob waste. After printing is complete, the porous paving blocks are dried in the sun and conditioned for approximately 21 days, then the porous paving blocks are ready to be tested. The experimental design consisted of 4 treatments, namely C1, C2, C3, and C4. For the density test, values were obtained with an average of 1.327 g/cm3 – 1.628 g/cm3. For the infiltration test, a value of 0.274 mm/s was obtained. Whereas the visible test is obtained with the appropriate form of paving texture obtained on factor C4 because the resulting texture is good and there are no gaps or defects when the paving has been printed. The highest value from the water absorption test occurred in the C4 treatment with a value of 23.91%. The effect of corncob waste on Porous Paving Blocks in this study is that the more corncob waste fiber is used, the more porous paving block cavities will be, and vice versa if using less corncob waste fiber, the pore cavities will be larger. produced on porous paving blocks will be less. Keywords: Corn Cogs, Paving block Porous.